An Innovative Approach to Improve Fire Protection During the Operation of Electrical Installations of the Production Process - Kh., Rasulev A.; J., Muxarramov O. (European Journal of Life Safety and Stability (2660-9630), 2021)
The development of technology is accompanied by a continuous increase in the level of consumption of electrical energy and the improvement of the equipment used. Electrical energy greatly facilitates and improves human labor and at the same time is a source of potential danger, which can lead to serious consequences.